(untitled) (Applied Research and Innovation, 2025)
The study was conducted in Adadle District of Shebelle Zone, Somali Regional State, with the objective of introducing and evaluating the productivity performance of improved beehives (modern and transitional) in comparison with the traditional hives commonly used by local beekeepers. A total of 25 experienced members of Pastoral and Agro-Pastoral Research Extension Groups (PAPREGs) were purposively selected to participate in this participatory research. Theoretical and practical training sessions on honeybee colony management were provided to both PAPREG members and local development agents. Both qualitative and quantitative data were collected and analyzed using descriptive statistics. During the first harvesting season, the average honey yield per hive was 3.63 kg for traditional hives and 10.5 kg for modern hives. In the second season, yields increased to 4.25 kg and 11.75 kg, respectively. The average annual honey yield was 7.88 kg per traditional hive and 22.25 kg per modern hive, showing a statistically significant difference (P<0.05), with improved hives yielding nearly three times more than traditional ones. PAPREG members highlighted high honey yield, ease of colony inspection, and simplified harvesting as the key advantages of improved hives. However, they also noted high initial cost, the need for technical skills, and additional accessories as relative limitations. Despite these challenges, the positive perception of improved technologies among beekeepers presents a valuable opportunity for apiculture development in the region. It is therefore recommended that improved beehive technologies be widely promoted and scaled up in areas where adoption remains low, to enhance honey production and improve livelihoods in pastoral and agro-pastoral communities.